1999
DOI: 10.1038/sj.sc.3100821
|View full text |Cite
|
Sign up to set email alerts
|

Ambulation training of neurological patients on the treadmill with a new Walking Assistance and Rehabilitation Device (WARD)

Abstract: Study design: Patients with neurological walking impairment were rehabilitated with a new system, consisting of an apparatus to constantly relieve the body weight and a treadmill: The Walking Assistance and Rehabilitation Device (WARD). Patients were evaluated before and after rehabilitation with clinical scales and physiological measurements. Objectives: To evaluate the eectiveness of the WARD in improving walking capability in these patients. Setting: The study was carried out in a clinical environment (IRCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 18 publications
0
11
1
Order By: Relevance
“…It has also been shown that the walk ratio (WR), which is expressed as the ratio between stride length (SL) and stride frequency (SF), a speed-independent index of walking pattern (Nagasaki et al 1996), is smaller in older individuals than their young counterparts due to a greater reduction in SL rather than SF (Kerrigan et al 1998;Winter et al 1990). An invariant WR at different walking speeds often characterises a normal walking pattern (Sekiya and Nagasaki 1998) and is optimal with respect to the energy cost (Zarrugh et al 1974) It has been demonstrated that training on a treadmill with an apparatus of body weight unloading (BWU) is an effective tool in the rehabilitation of both neurological (Dietz et al 1995;Gazzani et al 1999) and orthopaedic patients (Fritz et al 1997;Mangione et al 1996) with locomotor impairment. Unloading of a given percentage of body weight allows early mobilisation of patients who are unable to support their own body weight or stand erect due to neuromuscular weakness.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that the walk ratio (WR), which is expressed as the ratio between stride length (SL) and stride frequency (SF), a speed-independent index of walking pattern (Nagasaki et al 1996), is smaller in older individuals than their young counterparts due to a greater reduction in SL rather than SF (Kerrigan et al 1998;Winter et al 1990). An invariant WR at different walking speeds often characterises a normal walking pattern (Sekiya and Nagasaki 1998) and is optimal with respect to the energy cost (Zarrugh et al 1974) It has been demonstrated that training on a treadmill with an apparatus of body weight unloading (BWU) is an effective tool in the rehabilitation of both neurological (Dietz et al 1995;Gazzani et al 1999) and orthopaedic patients (Fritz et al 1997;Mangione et al 1996) with locomotor impairment. Unloading of a given percentage of body weight allows early mobilisation of patients who are unable to support their own body weight or stand erect due to neuromuscular weakness.…”
Section: Introductionmentioning
confidence: 99%
“…With a body weight support system, extraneous muscular contractions are reduced. 30 In previous studies, 16,18 EMG and kinematic recordings demonstrated that treadmill and body weight unloading reduce gait asymmetry as well as induce the acquisition of motor patterns similar to normal gait. In addition, the repetition and consistent nature of walking on a moving treadmill might help the patient to repeatedly practice the movement under controlled conditions.…”
Section: Discussionmentioning
confidence: 99%
“…27 Extraneous muscular contractions are also reduced with a body weight support system. 30 Evidence from EMG and kinematic recordings suggested that body weight unloading on the treadmill reduced gait asymmetry and induced the acquisition of a more normal gait. 16,18 The purpose of this case report is to report an 8-week rehabilitation program for a patient with PSP.…”
mentioning
confidence: 99%
“…The use of a treadmill in conjunction with a partial body weight unloading (BWU) apparatus has been shown to be effective in the rehabilitation of gait in both neurological [11] and orthopedic patients [12]. Thomas et al [13,14] have demonstrated that healthy older women can be successfully trained by walking on a treadmill at 40% BWU, thus achieving higher speeds than they would do in normal gravity conditions without increasing their energy and cardiac cost.…”
Section: Introductionmentioning
confidence: 98%